PERANAN CUSTOMER SERVICE DALAM MENINGKATKAN JUMLAH NASABAH PADA PT. BANK PEMBANGUNAN DAERAH JAWA BARAT DAN BANTEN, TBK. CAPEM PAMULANG TANGERANG SELATAN - Alida Wahyuni; Mungky Hendriyani; Intan Nurhasanah (Institut Teknologi dan Bisnis Swadharma, 2022)
This research aims to analyze the role of customer service in increasing the number of customers PT. Bank BJB, Tbk. Kantor Cabang Pembantu Pamulang. A customer is a person directly dealing with or in direct contact with the customer, customer service has a responsible role in the service and smoothness of the bank, and understands the work to be carried out, especially related to service to customers. Serving the customer is a very necessary attitude of customer service that can increase customer interest and ability to communicate well with customers. The results prove the role of customer service in providing information to customers very well. Because the media used customer service in providing the information is very good and customers feel very satisfied with the services provided by customer service